Konstruksi dan Historisitas Kampung Kasur Pasir sebagai Identitas Budaya dalam Menjaga Nilai-Nilai Tradisi Masyarakat Desa Legung Timur - Ilyasi, Moh.; Matroni, Matroni; Syafi'i, Imam (CV. Ulil Albab Corp, 2025)
This study explores the construction and historicity of cultural identity in Kampung Kasur Pasir in an effort to preserve the traditional values of the Legung Timur Village community. Using a qualitative approach through observation methods, in-depth interviews, and document analysis, this study finds that social interactions, community values, and historical elements significantly contribute to the formation of a dynamic cultural identity. The active participation of the younger generation in cultural activities, such as rituals and traditional celebrations, is seen as key to preserving traditions amid the challenges of modernization and globalization. The research results show that the people of Kampung Kasur Pasir not only maintain traditional rituals but also adapt new elements relevant to contemporary developments. Additionally, awareness of the importance of cultural preservation as an instrument of social solidarity is highly relevant. This study is expected to contribute to the development of more effective cultural preservation policies and encourage local initiatives in celebrating and maintaining a rich cultural heritage.